2014
DOI: 10.1055/s-0034-1382019
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of life after Corrective Surgery for Congenital Heart Disease

Abstract: Children with congenital heart defects are able to develop coping structures, that enable them to live a normal life from their individual point of view. Integration in psychosocial structures seems to be rather normal when compared to healthy controls. Many patients considered their HRQoL as even better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Healthcare advances now allow the correction or palliation of CHD, resulting in improved length and quality of life [4][5][6]. The timely diagnosis, appropriate treatment and long-term care for CHD patients is multi-disciplinary and depends on the availability of appropriately structured systems with adequate infrastructure [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare advances now allow the correction or palliation of CHD, resulting in improved length and quality of life [4][5][6]. The timely diagnosis, appropriate treatment and long-term care for CHD patients is multi-disciplinary and depends on the availability of appropriately structured systems with adequate infrastructure [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen institutions (46%) received periodic staff reinforcements through visiting cardiac surgical teams from abroad. The teams visited a median of two (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) times in a year.…”
Section: Staffingmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it should be taken into account that most quality-of-life studies with patients with CHD use different questionnaires. Furthermore, there is a major difference between self-reported and parent proxy-reported study design – parents tend to report a lower health-related quality of life of their child, 25,26 which may refer to the so-called “vulnerable child syndrome”. 21 Moreover, the age seems to be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…In the congenital heart disease (CHD) population, there have been conflicting results regarding QoL with some studies demonstrating decreased QoL 6 and others showing no difference between children with CHD and their healthy peers. 7 Similar to the overall CHD cohort, there are inconsistent data regarding QoL in the AAOCA population. In 2017, Sing et al reported on an unoperated AAOCA cohort at their institution using generic PedsQL surveys and found that, while the patients reported normal QoL, the parents of patients who were exercise-restricted reported decreased levels of physical functioning, general health perception, and emotional impact on the parent and physical summary scores.…”
mentioning
confidence: 99%